Evaluation of Ophthalmology Consultations of Inpatients In A Tertiary Pediatric Hospital - Ali Güngör; Serkan Özmen; Aydan Sezgin Ersoy; esin eyican; Bahar Çuhacı Çakır; Cüneyt Karagöl; Alkim Öden Akman (Galenos Publishing House, 2019)
INTRODUCTION: The eye can be affected by acute infections, traumas, primary eye diseases and may be affected by secondary to systemic diseases. The aim of this study is to evaluate the ophthalmology consultations of inpatients in our hospital between January 2016 and December 2017 and to determine the ocular findings in patients with chronic disease. METHODS: The age, gender, treatment, chronic disease of the patients whom consulted to the ophthalmology department were recorded. The reason for consultation to ophthalmology and examination findings were tried to be determined. RESULTS: 1514 (5.3%) of 28.556 inpatients were consulted to ophthalmology department between January 2016 and December 2017. Of these patients, 829 (54.76%) were male and the median age was 63.5 months (range 8-154). Of the 958 (63.28%) patients had chronic disease. In all patients, 92 (6.08%) patients had conjunctivitis, 47 (3.1%) had refractive errors, 44 (2.91%) had papillary edema and 26 (1.72%) had preseptal cellulitis. In addition, the anterior lenticonus, Lisch nodule, Kayser-Fleischer ring, Japanese flag appearance, uveitis findings, hypertensive retinopathy and ROP were the important findings of the examination. DISCUSSION AND CONCLUSION: As a result the eye involvement may be secondary to systemic diseases as well as primary diseases of the eye. In patients with chronic disease, it is important to perform regular eye examination in order to determine the involvement that may develop in the later stages even if there are no ocular signs.